Electron impact ionization and multiphoton ionization of doped superfluid helium droplets: A comparison - He, Yunteng (J Chem Phys, 2016)
We compare characteristics of electron impact ionization (EI) and multiphoton ionization (MPI) of doped superfluid helium droplets using the same droplet source. Selected dopant ion fragments from the two ionization schemes demonstrate different dependence on the doping pressure, which could be attributed to the different ionization mechanisms. While EI directly ionizes helium atoms in a droplet therefore has higher yields for bigger droplets (within a limited size range), MPI is insensitive to the helium in a droplet and is only dependent on the number of dopant molecules. The optimal timing of the ionization pulse also varies with the doping pressure, implying a velocity slip among different sized droplets. Calculations of the doping statistics and ionization probabilities qualitatively agree with the experimental data. Our results offer a word of caution in interpreting the pressure and timing dependence of superfluid helium droplets, and we also devise a scheme in achieving a high degree of doping while limiting the contribution of dopant clusters.